Expectations of work in the first level of health care students at a medical school in Lima, Peru - Tarqui Mamani, Carolina B. (2015)
Introduction: The health status of Peru requires more health professionals provide care in health facilities of primary care, mainly located in remote, rural or poorer areas of the country. Objective: To identify professional and personal expectations of future health professionals who are trained in a medical school in Lima, particularly work on the first level of health care. Design: observational, descriptive and exploratory study. Location: Faculty of Medicine, National University of San Marcos, Lima, Peru. Participants: Students pre boarding of Professional Academic Schools. Interventions: The convenience sample and included 278 students from five schools that make medical school. An ad hoc questionnaire with aspects relating to labor, economic and vision of students as future professionals wondered expectations was applied. Means, standard deviation, frequency distribution, confidence intervals at 95% with proof of Poisson and chi square was calculated. Main outcome measures: Expectation of work in the first level of health care. Results: 50% of students said they would like to develop in nursing care; only 14.5% expressed their intention to work on the first level of health care (health posts and centers), 87.1% considered a landmark study in college is a strength that favors their professional and 57.6% which will continue to graduate studies; 58.6% of students stated the intention to work in Lima, 21.9% and 16.2% in the provinces and abroad. The average monthly economic expectations was the equivalent of 1577 soles or just over 2 minimum wages vital planned for 2012. Conclusions: The expectation of future health professionals to work in local primary health care is come down.